An overview of menopausal symptoms using the menopause rating scale in a tertiary care center - Aisha Khatoon; Samia Husain; Sonia Husain; Saba Hussain (Wolters Kluwer Medknow Publications, 2018)
Context: Due to increased life expectancy worldwide, women are expected to spend a significant portion of their lives in menopause. Proven prevention strategies against serious risks and tested effective treatments for common symptoms may remain unutilized in our population if these women are not asked about these symptoms. Aim: This study aims to assess the prevalence of different menopausal symptoms and their severity according to menopause rating scale (MRS) in women. Setting and Design: The present study was a cross-sectional survey, conducted in the outpatient department of gynecology and obstetrics. Subjects and Methods: After written and informed consent, 121 women having their last menstrual period at least 1 year ago were included. The menopausal symptoms were assessed using the MRS. The primary outcome measure in this study was the prevalence of menopausal symptoms in these women according to MRS and the severity of these symptoms. Statistical Analysis Used: Data were analyzed using the SPSS software program, version 15.0 (IBM, Armonk, New York, USA). Results: The most common symptom was mental and physical exhaustion which was reported by 88 (72%) women, followed by joint and muscular discomfort which was reported by 83 (68.59%). Hot flushes were reported by 54 (44.62%) respondents. Majority of women reported mild-to-moderate symptoms. Conclusions: The prevalence of menopausal symptoms is high, and a health policy needs to be generated for the region.